Design and Construction of the Auenbach Bridge, Austria - Geier, Roman (Structural engineering international : journal of the International Association for Bridge and Structural Engineering (IABSE), 2010)
In 2007, one of the largest composite bridges in Austria was built as part of the upgrading of the A2 motorway. First a steel skeleton 700 m long was extended from the two abutments on piers 70 m high; then concrete was cast in situ to complete the load-bearing structure. The geometry of the site necessitated special fabrication methods. With caissons located in an incline subject to slip, and the need to allow for earthquakes, planning the structure was an extremely demanding task, involving non-linear calculation of supports as per second-order theory, taking into account state 2 and the various loads imposed during erection. This paper summarizes the main issues affecting design and construction.